Solid electrolyte membrane and preparation method thereof

By adding ionic conductive adhesives and polymers to the solid electrolyte membrane to form a self-supporting structure, the problems of mechanical stability and ion transport efficiency of the solid electrolyte membrane are solved, and the electrochemical performance and service life of the solid battery are improved.

CN119253052APending Publication Date: 2025-01-03CHINA AUTOMOTIVE INNOVATION CORP
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411482437.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The solid electrolyte membrane of solid-state batteries is prone to large particle gaps and high porosity under high pressure, which affects ion transmission efficiency, and has poor mechanical stability, which can easily lead to fracture, resulting in low battery charging and discharging efficiency and poor first-term effect.

Method used

A solid electrolyte membrane including electrolyte materials, ionic conductive binders and polymers is used to form a self-supporting structure through in-situ polymerization, which improves mechanical stability and flexibility, increases the ionic conductivity of lithium salts, and shortens the ion transmission path.

Benefits of technology

It improves the ionic conductivity and mechanical stability of the solid electrolyte membrane, enhances the electrochemical performance and cyclic stability of the battery, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119253052A_ABST
    Figure CN119253052A_ABST
Patent Text Reader

Abstract

The invention discloses a solid electrolyte membrane and a preparation method, the solid electrolyte membrane comprises an electrolyte material, an ionic conductive binder and a polymer, the ionic conductive binder comprises a binder and a lithium salt, and the polymer is obtained by in-situ polymerization of a polymer monomer in a membrane forming process. The polymer and the conductive ion binder can fill gaps of electrolyte particles, so that the flexibility of the solid electrolyte membrane is improved, and the solid electrolyte membrane can bear higher pressure; and an ion transmission channel can be shortened, so that the ionic conductivity of the solid electrolyte membrane is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of composite materials, and in particular to a solid electrolyte membrane and a preparation method thereof. Background Art

[0002] Solid-state lithium battery technology uses a glass compound made of lithium and sodium as a conductive material, and uses a solid electrolyte to replace the electrolyte of previous lithium batteries. Compared with traditional liquid batteries, solid-state batteries exhibit higher safety under high temperatures and mechanical stress; compared with liquid electrolytes with the same lithium content, solid electrolytes are lighter, allowing the battery anode material to use high-gram capacity materials, which can greatly increase the energy density of the battery; in terms of cycling, the interface between the solid-state electrolyte and the electrode material is more stable, which can reduce the occurrence of side reactions, thereby extending the service life of the battery; solid-state batteries have a wider operating temperature range, and the solid electrolyte is not easy to freeze or evaporate, allowing the battery to work normally under more extreme temperature conditions.

[0003] Although solid-state batteries have significant advantages in terms of safety, energy density and cycle life, the current research and development of solid-state batteries still faces difficulties. As an important component of all-solid-state batteries, solid electrolytes connect the positive and negative electrodes and become the transportation channel for lithium ions. In solid electrolytes, most polymer binders are insulators, which are non-conductive and non-ion-conductive, which seriously affects the transmission efficiency of lithium ions, resulting in high battery impedance, slow battery charging and discharging efficiency and low initial efficiency. In the preparation process, the solid electrolyte is placed under high pressure to increase the compaction density of the electrolyte membrane, making the contact with the positive and negative electrodes closer and reducing the interface impedance, but high pressure will cause large gaps between the solid electrolyte particles, making the electrolyte membrane porosity higher, which is not conducive to ion transmission. If the pressure continues to increase, the electrolyte membrane will break due to the inability to withstand stress. Therefore, it is urgent to solve the above problems and improve the flexibility and ionic conductivity of the solid electrolyte membrane. Summary of the invention

[0004] In view of the above problems in the prior art, the present application provides a solid electrolyte membrane and a preparation method thereof, and the specific technical solutions are as follows:

[0005] On the one hand, the present application provides a solid electrolyte membrane, characterized in that the solid electrolyte membrane includes an electrolyte material, an ion conductive binder and a polymer, the ion conductive binder includes a binder and a lithium salt, and the polymer is obtained by in-situ polymerization of polymer monomers during the film formation process.

[0006] In a possible implementation manner, the solid electrolyte membrane satisfies at least one of the following characteristics:

[0007] The mass ratio of the electrolyte material, the ion conductive binder and the polymer in the solid electrolyte membrane is 90-98:1-9:0.2-1;

[0008] The mass ratio of the binder to the lithium salt in the ion conductive binder is 99-99.7:0.3-1.

[0009] In a possible implementation manner, the electrolyte membrane has a thickness of 5-100 μm.

[0010] In a possible implementation manner, the solid electrolyte membrane satisfies at least one of the following characteristics:

[0011] The polymer monomer includes at least one of vinyl carbonate, vinyl sulfite, vinylene trithiocarbonate, 1,3-propylene-sultone, propylene ethyl carbonate, diester of formate, allylphenyl carbonate, methyl methacrylate, and vinyl acetate;

[0012] The electrolyte material includes at least one of an Argentum-type sulfide solid electrolyte and a Thio-LISION-type sulfide solid electrolyte;

[0013] The binder comprises at least one of ethyl cellulose, poly(1,4-butylene adipate), poly(ethylene butylene), polyacrylic acid and polyacrylonitrile;

[0014] The lithium salt includes at least one of lithium hexafluorophosphate, bis(fluorosulfonyl)imide lithium salt, bis(trifluoromethanesulfonyl)imide lithium, and bis(pentafluoroethylsulfonyl)imide lithium.

[0015] In a possible implementation manner, the electrolyte material satisfies at least one of the following characteristics:

[0016] The argyrodite-type sulfide solid electrolyte includes Li6PS5X, wherein X includes at least one of Cl, Br, and I;

[0017] The Thio-LISION type sulfide solid electrolyte includes (100-x)Li2S-xP2S5, Li4-yA-yB y S4, Li4SnS4 and X-doped Thio-LISION type sulfide solid electrolyte, wherein 0<x<100, A includes at least one of Ge and Si, B includes at least one of P, Al or Zn, 0<y<1, and x includes at least one of I and Br.

[0018] On the other hand, a method for preparing the solid electrolyte membrane as described above is provided, the preparation method comprising:

[0019] Providing electrolyte slurry, ion conductive adhesive solution, polymer monomer solution and polymer initiator solution;

[0020] The electrolyte slurry, the ion conductive binder, the polymer monomer solution and the polymer initiator solution are mixed according to a proportion, ground and dispersed to obtain a mixed solution;

[0021] The mixed solution is coated on a bottom plate and heated to obtain a solid electrolyte membrane.

[0022] In a possible implementation manner, the electrolyte slurry includes an electrolyte material and a solvent, and the electrolyte material accounts for 20%-50% by weight of the electrolyte slurry.

[0023] In a possible implementation manner, the ion conductive adhesive glue comprises a binder, a lithium salt and a solvent, and the ion conductive adhesive satisfies at least one of the following characteristics:

[0024] The binder and the lithium salt account for 5%-10% by mass in the ion conductive binder solution;

[0025] The solvent includes at least one of xylene, trimethylbenzene, chlorobenzene, dichlorobenzene, trichlorobenzene, isobutyl isobutyrate, butyl acetate, anisole, and dibutyl ether.

[0026] In a possible implementation manner, the polymer monomer solution includes a polymer monomer, a lithium salt and a solvent, and the polymer monomer solution satisfies at least one of the following characteristics:

[0027] The mass ratio of the polymer monomer to the lithium salt is 99.5-99.7:0.3-0.5;

[0028] The polymer monomer and the lithium salt account for 40%-60% by mass in the polymer monomer solution;

[0029] The solvent includes at least one of xylene, trimethylbenzene, chlorobenzene, dichlorobenzene, trichlorobenzene, isobutyl isobutyrate, butyl acetate, anisole, and dibutyl ether.

[0030] In a possible implementation manner, the polymer initiator solution includes a polymer initiator and a solvent, and the polymer initiator solution satisfies at least one of the following characteristics:

[0031] The mass proportion of the polymer initiator in the polymer initiator solution is 10%-50%;

[0032] The polymerization initiator includes at least one of benzoyl peroxide, diisopropyl peroxydicarbonate, azobisisobutyronitrile and tris(trifluoromethyl-sulfonate)aluminum.

[0033] In a possible implementation manner, the preparation method satisfies at least one of the following characteristics:

[0034] The mass ratio of the electrolyte material, the ion conductive binder, the polymer monomer and the polymer initiator is 90-98:1-9:0.1-0.5:0.1-0.5;

[0035] The solid content of the mixed solution is 30%-50%;

[0036] The mixing and grinding and dispersing processes are carried out at 10-20°C;

[0037] The heating temperature is 90-120°C;

[0038] The heating time is 10-16h.

[0039] Based on the above technical solution, this application has the following beneficial effects:

[0040] 1. The present application adds an ion conductive binder to the solid electrolyte membrane. The ion conductive binder includes a binder and a lithium salt, which is beneficial to improving the bonding force between the electrolyte particles to improve the mechanical stability of the electrolyte membrane. Due to the addition of the lithium salt, the binder is endowed with ionic conductivity, which increases the ion transmission channels in the solid electrolyte membrane and shortens the ion transmission path, thereby improving the ionic conductivity of the solid electrolyte membrane.

[0041] 2. During the film formation process of the solid electrolyte membrane of the present application, the polymer monomer is obtained by in-situ polymerization reaction, and the polymer is reacted with the ion conductive binder to form a self-supporting structure in the solid electrolyte membrane, thereby providing mechanical support for the solid electrolyte membrane, which is beneficial to improving the mechanical stability of the solid electrolyte membrane; and the polymer and the conductive ion binder can fill the gaps between the electrolyte particles, reduce the porosity of the solid electrolyte membrane, and improve the flexibility of the solid electrolyte membrane, so that the solid electrolyte membrane can withstand higher pressure during the compaction process, which is beneficial to improving the compaction density of the solid electrolyte membrane, reducing the interface impedance of the solid electrolyte membrane in contact with the positive and negative electrodes, and thereby improving the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0043] Figure 1: A SEM image of a solid electrolyte membrane after isostatic pressing provided in Example 1 of the present application;

[0044] Figure 2 : An SEM image of a solid electrolyte membrane after isostatic pressing treatment provided in Comparative Example 4 of the present application. DETAILED DESCRIPTION

[0045] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0046] For the following defined terms, these definitions shall apply unless a different definition is given in the claims or elsewhere in this specification. All numerical values, whether or not explicitly indicated, are defined herein as modified by the term "about". The term "about" generally refers to a numerical range that a person of ordinary skill in the art considers to be equivalent to the stated values ​​to produce substantially the same properties, functions, results, etc. A numerical range indicated by a lower value and a higher value is defined to include all numerical values ​​included in the numerical range and all subranges included in the numerical range.

[0047] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.

[0048] The following introduces a solid electrolyte membrane provided in an embodiment of the present application, wherein the solid electrolyte membrane includes an electrolyte material, an ion conductive binder and a polymer, wherein the ion conductive binder includes a binder and a lithium salt, and the polymer is obtained by in-situ polymerization of polymer monomers during the film formation process.

[0049] Based on the above scheme, the ion conductive binder in the solid electrolyte membrane can improve the adhesion between the electrolyte particles, improve the structural stability and safety performance of the electrolyte membrane; and the ion conductive binder provides more channels for ion transmission, shortens the ion transmission path, and thus improves the ion conductivity of the electrolyte membrane. The polymer monomer is obtained by in-situ polymerization during the film formation process of the solid electrolyte membrane. The polymer forms a self-supporting structure with the ion conductive binder in the solid electrolyte membrane, fills the gaps between the electrolyte particles, improves the flexibility and mechanical stability of the solid electrolyte membrane, helps the solid electrolyte membrane resist higher pressure, prevents the electrolyte membrane from cracking or breaking, and thus improves the safety performance and service life of the solid electrolyte membrane.

[0050] Specifically, the mass ratio of the electrolyte material, the ion conductive binder and the polymer in the solid electrolyte membrane is 90-98:1-9:0.2-1; it can be understood that the mass ratio of the electrolyte material, the ion conductive binder and the polymer in the solid electrolyte membrane can be any point value in 90-98:1-9:0.2-1; illustratively, the mass ratio of the electrolyte material, the ion conductive binder and the polymer in the solid electrolyte membrane can be 90:9:1, 90.8:9:0.2, 94.5:5:0.5, 98:1.8:0.2, 98:1:1, etc. Controlling the mass ratio of electrolyte materials, ion conductive binders and polymers within the above range is beneficial to improving the film formation reliability and mechanical strength of the solid electrolyte membrane after film formation; among them, the high mass proportion of electrolyte materials in the solid electrolyte membrane can improve the ion transmission efficiency, which is beneficial to improving the conductive properties of the solid electrolyte membrane, thereby improving the charge and discharge performance of the solid-state battery having the solid electrolyte membrane; ion conductive binders and polymers can improve the flexibility and structural stability of the solid electrolyte membrane on the basis of ensuring that the solid electrolyte membrane has a high ionic conductivity, thereby improving the cycle stability and service life of the solid-state battery.

[0051] Specifically, the mass ratio of the binder and the lithium salt in the ion conductive binder is 99-99.7:0.3-1; it can be understood that the mass ratio of the binder and the lithium salt in the ion conductive binder can be any point value in 99-99.7:0.3-1; illustratively, the mass ratio of the binder and the lithium salt in the ion conductive binder can be 99:1, 99.2:0.8, 99.3:0.7, 99.5:0.5, 99.7:0.3, etc. In this way, by controlling the mass ratio of the binder and the lithium salt within the above range, the ion conductive binder can play a bonding role between the electrolyte particles, provide more ion transmission channels required in the solid electrolyte membrane, shorten the ion transmission path, and improve the ion conductivity of the solid electrolyte membrane, which is conducive to improving the charge transfer rate and reaction speed of the solid-state battery having the solid electrolyte membrane, and enhancing the electrochemical performance and output efficiency of the solid-state battery.

[0052] Specifically, the thickness of the solid electrolyte membrane is 5-100 μm. It can be understood that the thickness of the solid electrolyte membrane can be any point value in the range of 5-100 μm; illustratively, the thickness of the solid electrolyte membrane can be 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, etc. Controlling the thickness of the solid electrolyte membrane within the above range can make the solid electrolyte membrane have higher ion conductivity and better safety. If the thickness of the solid electrolyte membrane is less than 5 μm, the migration path of ions in the solid electrolyte membrane is shorter, and the electrolyte membrane has higher ion conductivity. However, the mechanical strength of the too thin solid electrolyte membrane is insufficient, which makes the solid electrolyte membrane easy to break during use, affecting the safety of the solid electrolyte membrane; if the thickness of the solid electrolyte membrane is greater than 100 μm, it will increase the resistance of ion transmission, resulting in reduced electrochemical performance of the solid electrolyte membrane.

[0053] Specifically, the electrolyte material includes at least one of an Argentum-type sulfide solid electrolyte and a Thio-LISION-type sulfide solid electrolyte.

[0054] Preferably, the argyrodite-type sulfide solid electrolyte includes Li6PS5X, wherein X includes at least one of Cl, Br, and I.

[0055] Preferably, the Thio-LISION type sulfide solid electrolyte comprises (100-x)Li2S-xP2S5, Li4-yA-yB yS4, Li4SnS4 and X doped Thio-LISION type sulfide solid electrolyte, wherein 0<X<100, A includes at least one of Ge and Si, B includes at least one of P, Al or Zn, 0<y<1, x includes at least one of I and Br. Sulfide solid electrolyte has high ionic conductivity, which is beneficial to improve the ion transport capacity of the solid electrolyte membrane, thereby improving the charge and discharge rate of the solid-state battery with the solid electrolyte membrane, and improving the cycle stability of the solid-state battery.

[0056] Specifically, the polymer monomer includes at least one of vinyl carbonate, vinyl vinyl sulfite, vinylene trithiocarbonate, 1,3-propylene-sultone, propylene ethyl carbonate, diester, allylphenyl carbonate, methyl methacrylate, and vinyl acetate. The polymer monomer can undergo an in-situ polymerization reaction under the action of an initiator and heating. The polymer generated by the reaction forms a self-supporting structure in the solid electrolyte membrane, which can effectively support and protect the internal structure of the solid electrolyte membrane. The polymer can fill the gaps between the electrolyte particles, which is beneficial to improving the flexibility of the solid electrolyte membrane.

[0057] Specifically, the binder includes at least one of ethyl cellulose, poly(1,4-butylene adipate), polyethylene, polyacrylic acid, and polyacrylonitrile; the binder can effectively increase the adhesion between electrolyte particles, ensure close contact between electrolyte materials, fix the internal structure of the solid electrolyte membrane, and prevent the solid electrolyte membrane from cracking or breaking; and has good chemical stability, and can still keep the solid electrolyte membrane intact after long-term use, preventing the internal solid electrolyte from pulverizing and falling off, which causes the battery performance to plummet.

[0058] Specifically, the lithium salt includes at least one of lithium hexafluorophosphate, bis(fluorosulfonyl)imide lithium salt, bis(trifluoromethanesulfonyl)imide lithium, and bis(pentafluoroethylsulfonyl)imide lithium. The lithium salt can be highly dissociated to increase the lithium ion concentration and provide more lithium ions. When combined with a binder, it can enhance the conductivity of the binder, shorten the transmission path of lithium ions in the solid electrolyte membrane, and improve the lithium ion transmission efficiency, thereby greatly improving the conductivity of the solid electrolyte membrane.

[0059] The embodiment of the present application also provides a method for preparing a solid electrolyte membrane, by which the above-mentioned solid electrolyte membrane is prepared. This specification provides the method operation steps as in the embodiment, but more or fewer operation steps may be included based on conventional or non-creative labor. The order of steps listed in the embodiment is only one way of executing the order of many steps and does not represent the only execution order. When the actual preparation method is executed, it can be executed in the order of the method shown in the embodiment or the accompanying drawings or in parallel. Specifically including the following steps:

[0060] S1: providing electrolyte slurry, ion conductive adhesive solution, polymer monomer solution and polymer initiator solution;

[0061] S2: mixing the electrolyte slurry, the ion conductive binder glue, the polymer monomer solution and the polymer initiator solution according to a proportion, grinding and dispersing them to obtain a mixed solution;

[0062] S3: coating the mixed solution on a bottom plate and heating it to obtain a solid electrolyte membrane.

[0063] Among them, in step S1, electrolyte slurry, ion conductive binder glue, polymer monomer solution and polymer initiator solution are prepared; in step S2, the above solutions are mixed and ground and dispersed, so that each material is evenly dispersed and fully contacted in the mixed solution, which is beneficial to improve the uniformity of film formation and is beneficial to the polymerization reaction in the subsequent film formation process; in step S3, the mixed solution is coated and heated to form a film to obtain a solid electrolyte membrane with uniform and controllable thickness, which can be cut into any shape and size, and is more convenient to use at the battery end.

[0064] Among them, the in-situ polymerization reaction occurs during the coating process of the mixed solution. The polymer initiator generates free radicals through thermal decomposition. The free radicals can further initiate the polymerization reaction of the polymer monomer molecules to form polymer chains, and then form cross-linked and cured polymers in the mixed solution after coating, filling the gaps between the electrolyte materials, playing a supporting role in the solid electrolyte membrane, and helping to improve the structural stability and flexibility of the solid electrolyte membrane.

[0065] In some embodiments, in step S1, the electrolyte material and the solvent are mixed in proportion and ground to obtain an electrolyte slurry.

[0066] Specifically, the mass ratio of the electrolyte material in the electrolyte slurry is 20%-50%. It can be understood that the mass ratio of the electrolyte material in the electrolyte slurry is any point value between 20% and 50%. Exemplarily, the mass ratio of the electrolyte material in the electrolyte slurry is 20%, 25%, 30%, 40%, 50%, etc. When the mass ratio of the electrolyte material is controlled within the above range, the electrolyte material can be dispersed in the solution, which is conducive to the coating of the electrolyte slurry into a film and improves the film forming efficiency.

[0067] Among them, the grinding treatment can be ball milling. Specifically, the ball milling includes at least one of agitated ball milling and planetary ball milling. Correspondingly, the solid electrolyte material can be ball milled by at least one of the agitated ball mill and the planetary ball mill, which can effectively crush the electrolyte material and refine the electrolyte material particles, which is beneficial to reducing the gap size between the electrolyte particles in the solid electrolyte membrane. At the same time, it can increase the contact area between the electrolyte material and the ion conductive binder, increase the bonding force between the electrolyte particles, and thus improve the mechanical strength and flexibility of the solid electrolyte membrane.

[0068] Preferably, the ball milling time is 1-5h, and the ball mill speed is 5-50rpm; it is understandable that the ball milling time can be any point value in 1-5h, and the ball mill speed can be any point value in 5-50rpm; illustratively, the ball milling time can be 1h, 2h, 3h, 4h, 5h, etc., and the ball milling speed can be 5rpm, 15rpm, 25rpm, 35rpm, 50rpm, etc. In this way, controlling the ball milling time and the ball mill speed within the above range can effectively refine the electrolyte particles, improve the dispersibility of the electrolyte material in the solution, facilitate the subsequent sufficient mixing of the ion conductive binder glue, polymer monomer solution, polymer initiator solution and electrolyte slurry, and improve the distribution uniformity of the electrolyte material in the mixed solution.

[0069] In some embodiments, in step S1, a binder, a lithium salt, and a solvent are mixed according to a ratio and heated to obtain an ion conductive binder paste.

[0070] Specifically, the mass ratio of the binder to the lithium salt is 99-99.7:0.3-1; it is understandable that the mass ratio of the binder to the lithium salt can be any value in the range of 99-99.7:0.3-1, which will not be described in detail here. In this way, the lithium salt is evenly dispersed in the binder, which can improve the ionic conductivity of the binder.

[0071] Specifically, the mass proportion of the binder and the lithium salt in the ion conductive binder glue is 5%-10%; it can be understood that the mass proportion of the binder and the lithium salt in the ion conductive binder glue can be any point value between 5% and 10%; illustratively, the mass proportion of the binder and the lithium salt in the ion conductive binder glue is 5%, 6%, 7%, 8%, 9%, 10%, etc. In this way, controlling the mass proportion of the binder and the lithium salt in the ion conductive binder glue within the above range can improve the wettability of the ion conductive binder glue, which is beneficial to the full mixing of the ion conductive binder glue and the electrolyte slurry.

[0072] Specifically, the solvent includes at least one of xylene, trimethylol, chlorobenzene, dichlorobenzene, trichlorobenzene, isobutyl isobutyrate, butyl acetate, anisole, and dibutyl ether, which can swell the binder and dissolve the lithium salt, so that the binder and the lithium salt are fully mixed, and the ion conductive binder has good wettability, which is beneficial to improve the mixing uniformity of the ion conductive binder and the electrolyte slurry.

[0073] Specifically, the heating temperature of the ion conductive binder is 90-120°C, and the heating time is 15-30min; it can be understood that the heating temperature can be any point value in the range of 90-120°C, and the heating time can be any point value in the range of 15-30min; for example, the heating temperature is 90°C, 95°C, 100°C, 110°C, 120°C, etc., and the heating time can be 15min, 17min, 20min, 25min, 30min, etc. In this way, controlling the heating temperature and heating time within the above range can make the binder swell, which is conducive to promoting the movement of the binder molecular segments, improving the adhesion and stability of the binder, and then improving the adhesion between the electrolyte materials to improve the mechanical stability of the solid electrolyte membrane.

[0074] In some embodiments, in step S1, polymer monomers, lithium salts and solvents are mixed according to a ratio to obtain a polymer monomer solution.

[0075] Specifically, the mass ratio of the polymer monomer to the lithium salt is 99.5-99.7:0.3-0.5; it can be understood that the mass ratio of the polymer monomer to the lithium salt can be any point value in 99.5-99.7:0.3-0.5; illustratively, the mass ratio of the polymer monomer to the lithium salt can be 99.5:0.5, 99.55:0.45, 99.6:0.4, 99.65:0.35, 99.7:0.3, etc.; in this way, the addition of lithium salt can increase the lithium ion concentration, provide more lithium ions, and improve the conductivity of the polymer monomer after in-situ polymerization.

[0076] Specifically, the mass proportion of the polymer monomer and the lithium salt in the polymer monomer solution is 40%-60%; it can be understood that the mass proportion of the polymer monomer and the lithium salt in the polymer monomer solution can be any point value between 40% and 60%; illustratively, the mass proportion of the polymer monomer and the lithium salt in the polymer monomer solution can be 40%, 45%, 50%, 55%, 60%, etc.; in this way, the polymer monomer and the lithium salt are well dispersed in the solvent.

[0077] Specifically, the solvent includes at least one of xylene, trimethylol, chlorobenzene, dichlorobenzene, trichlorobenzene, isobutyl isobutyrate, butyl acetate, anisole, and dibutyl ether, which can dissolve polymer monomers and lithium salts and is conducive to the full mixing of the polymer monomer solution with the electrolyte slurry and the ion conductive adhesive.

[0078] In some embodiments, in step S1, the polymer initiator and the solvent are mixed according to a ratio to obtain a polymer initiator solution.

[0079] Specifically, the polymerization initiator includes at least one of benzoyl peroxide, diisopropyl peroxydicarbonate, azobisisobutyronitrile and tris(trifluoromethyl-sulfonic acid)aluminum, which can promote the polymerization of the polymer monomer and accelerate the polymerization reaction rate.

[0080] Specifically, the mass proportion of the polymer initiator in the polymer initiator solution is 10%-50%; it can be understood that the mass proportion of the polymer initiator in the polymer initiator solution can be any point value between 10%-50%; illustratively, the mass proportion of the polymer initiator in the polymer initiator solution can be 10%, 20%, 30%, 30%, 50%, etc.; in this way, the polymer initiator is effectively dispersed, which is beneficial to the subsequent full contact with the polymer monomer and improves the efficiency of the polymerization reaction.

[0081] In some embodiments, in step S2, the electrolyte slurry, the ion conductive binder glue, the polymer monomer solution and the polymer initiator solution are mixed according to a ratio, and the mass ratio of the electrolyte material, the ion conductive binder, the polymer monomer and the polymer initiator in the obtained mixed solution is 90-98:1-9:0.1-0.5:0.1-0.5; it can be understood that the mass ratio of the electrolyte material, the ion conductive binder, the polymer monomer and the polymer initiator can be any point value in 90-98:1-9:0.1-0.5:0.1-0.5; illustratively, the electrolyte material, the ion conductive binder, the polymer monomer and the polymer initiator are 90-98:1-9:0.1-0.5:0.1-0.5. The mass ratio of the sub-conductive binder, the polymer monomer and the polymer initiator can be 90:9:0.5:0.5, 90.4:9:0.1:0.5, 94.5:4.9:0.1:0.5, 98:1.5:0.3:0.2, 98:1:0.5:0.5, etc.; in this way, the polymer monomer in the mixed solution can fully react under the action of the polymer initiator, and the mass ratio of each component in the mixed solution is within the above range, which can make the solid electrolyte membrane have better flexibility and higher ionic conductivity, thereby improving the performance of the solid-state battery having the solid electrolyte membrane.

[0082] Specifically, the solid content in the mixed solution is 30%-50%; it can be understood that the solid content in the mixed solution can be any point value between 30%-50%; illustratively, the solid content in the mixed solution can be 30%, 35%, 40%, 45%, 50%, etc.; controlling the solid content in the mixed solution within the above range is beneficial to improving the uniformity and controllability of subsequent coating and film formation. If the solid content in the mixed solution is higher than the above range, the mixed solution is too thick, resulting in uneven film thickness; if the solid content in the mixed solution is lower than the above range, the solution fluidity is high, resulting in difficulty in controlling the film thickness.

[0083] Specifically, in step S2, the mixed solution is ground and dispersed. Preferably, the grinding method can be ball milling, the ball milling time is 10-30min, and the ball milling speed is 5-50rpm; it can be understood that the ball milling time can be any point value in 10-30min, and the ball milling speed can be any point value in 5-50rpm; illustratively, the ball milling time can be 10min, 15min, 20min, 25min, 30min, etc., and the ball milling speed can be 5rpm, 10rpm, 20rpm, 30rpm, 40rpm, etc.; in this way, the electrolyte material, ion conductive binder, polymer monomer and polymer initiator can be effectively dispersed, the uniformity of the mixed solution is improved, and then the distribution uniformity of each material in the solid electrolyte membrane after coating is improved, which is beneficial to improve the structural stability of the solid electrolyte membrane.

[0084] Specifically, the solution mixing process and the mixed solution grinding and dispersion process in step S2 are both carried out at 10-20°C; it can be understood that the ambient temperature can be any point value in 10-20°C, which will not be elaborated here. In this way, controlling the ambient temperature within the above temperature range can inhibit the occurrence of in-situ polymerization reaction during the mixing and grinding and dispersion processes, prevent the polymer monomers from polymerizing in the solution, and facilitate the polymer monomers to polymerize to form a self-supporting structure during the film formation process.

[0085] In some embodiments, the mixed solution obtained in step S2 is coated on a substrate, and the coated substrate includes at least one of steel foil, PET and PTFE. The coated substrate has good chemical stability and can withstand various chemicals during the wet coating process. The coated substrate has good thermal stability and can withstand a certain range of temperatures during the wet coating process. At the same time, it has good strippability, ensuring the integrity of the solid electrolyte membrane after stripping, which is beneficial to improving the production efficiency of the solid electrolyte membrane.

[0086] Specifically, the coating method can be blade coating, and correspondingly, the mixed solution is coated on the substrate by a blade coater, the blade coater includes a blade and a heatable bottom plate, the coated substrate is placed on the heatable bottom plate, the mixed solution can be evenly coated on the substrate by moving the blade, and the thickness of the coating can be controlled by controlling the specifications of the blade and the coating speed. The use of the blade coating method is conducive to improving the uniformity of the film formation of the solid electrolyte membrane and regulating the thickness of the solid electrolyte membrane; the heatable bottom plate of the blade coater can heat the coated wet film to obtain a solid electrolyte membrane, which is easy to operate and conducive to improving production efficiency.

[0087] Preferably, in the scraper coating method, the scraper specification is 5-200μm, and the coating speed is 8-20mm / s; it can be understood that the scraper specification can be any point value in 5-200μm, and the coating speed is any point value in 8-20mm / s; for example, the scraper specification can be 5μm, 10μm, 100μm, 150μm, 200μm, etc., and the coating speed can be 8mm / s, 10mm / s, 12mm / s, 14mm / s, 20mm / s, etc.; in this way, the scraper specification and coating speed are controlled within the above range, and a solid electrolyte membrane with a thickness range of 5-100μm can be obtained after heating. The coating method is simple to operate, and the thickness of the prepared solid electrolyte membrane is uniform and controllable, and it can be cut and made according to the designed size, and it is convenient to use at the battery end.

[0088] Specifically, the wet film after coating is heated, the heating temperature is 90-120°C, and the heating time is 10-16h; it can be understood that the heating temperature can be any point value in 90-120°C, and the heating time can be any point value in 10-16h; for example, the heating temperature can be 90°C, 95°C, 100°C, 110°C, 120°C, etc., and the heating time can be 10h, 11h, 12h, 14h, 16h, etc.; in this way, controlling the heating temperature and heating time within the above range is conducive to the in-situ polymerization reaction of the polymer monomer in the mixed solution. If the heating temperature and time are lower than the above range, the in-situ polymerization reaction may be insufficient, and the polymer cannot form a self-supporting structure; if the heating temperature and time exceed the above range, excessive heating will destroy the structure of the electrolyte material and the binder, affecting the electrochemical properties and mechanical stability of the electrolyte membrane. And within the above heating temperature and time, the solvent in the mixed solution can be removed, so that the electrolyte material, ion conductive binder and polymer form a film on the substrate.

[0089] In some embodiments, the solid electrolyte membrane is subjected to isostatic pressing at a pressure of 0-600 MPa; it can be understood that the pressure can be any point value in the range of 0-600 MPa; illustratively, the pressure can be 50 MPa, 100 MPa, 200 MPa, 400 MPa, 600 MPa, etc. Within the above pressure range, the solid electrolyte membrane can maintain a complete structure, and the structure of the solid electrolyte membrane is more compact after being subjected to mechanical stress, which is conducive to improving the compaction density of the solid electrolyte membrane and effectively improving the energy density and electrochemical performance of the battery having the solid electrolyte.

[0090] The following is an introduction to the specific embodiments of the present application in conjunction with the above-mentioned solid electrolyte membrane and preparation method. The following embodiments describe the technical solution of the present application in more detail, and these embodiments are only for illustrative purposes, because various modifications and changes within the scope of the disclosure of the present application are obvious to those skilled in the art. The reagents used in the embodiments can be obtained commercially or synthesized according to conventional methods, and can be used directly without further treatment, and the instruments and devices used in the embodiments can be obtained commercially.

[0091] Example 1

[0092] The solid electrolyte membrane of this embodiment is prepared by the following steps:

[0093] 1. Mix Li6PS5Cl electrolyte powder (LPSC) with xylene solvent, wherein the mass proportion of LPSC is 40%, and perform ball milling for 1-5h at a ball milling speed of 100-300rpm to obtain electrolyte slurry;

[0094] 2. Ethyl cellulose (EC) and lithium bis(fluorosulfonyl)imide (LiFSI) are mixed in a mass ratio of 99:1, xylene solvent is added, and the mixture is heated at a temperature of 90-120° C. for 15-30 min to obtain an ion conductive adhesive glue;

[0095] 3. Vinyl carbonate and LiFSI were mixed in a mass ratio of 99.5:0.5, and xylene solvent was added to obtain a polymer monomer solution;

[0096] 4. Mix diisopropyl peroxydicarbonate and xylene solvent in a mass ratio of 2:3 to obtain a polymer initiator solution;

[0097] 5. The electrolyte slurry, ion conductive binder, polymer monomer solution and polymer initiator solution are mixed, wherein the mass ratio of LPSC, EC / LiFSI, vinyl carbonate / LiFSI and diisopropyl peroxydicarbonate is 94.5:5:0.3:0.2, and the solid content is 35%, to obtain a mixed solution;

[0098] 6. The mixed solution was coated on a steel foil with a scraper specification of 90 μm and a coating speed of 10 mm / s. The bottom plate heating temperature of the coating machine was set to 90°C and the heating time was 12 h to obtain a solid electrolyte membrane with a thickness of 15 μm.

[0099] Among them, during the solid electrolyte film formation process, the polymer monomers undergo in-situ polymerization reaction, and the mass ratio of LPSC, EC / LiFSI, and polyvinyl carbonate / LiFSI in the obtained solid electrolyte membrane is 94.5:5:0.5.

[0100] Example 2

[0101] This embodiment provides a solid electrolyte membrane. The similarities with Example 1 are not repeated here. The difference from Example 1 is that during the coating process of the mixed solution, the scraper used has a specification of 200 μm, and after heating, a solid electrolyte membrane with a thickness of 80 μm is obtained.

[0102] Example 3

[0103] This embodiment provides a solid electrolyte membrane. The similarities with Example 1 are not repeated here. The difference from Example 1 is that the mass ratio of LPSC, EC / LiFSI, vinyl carbonate / LiFSI and diisopropyl peroxydicarbonate in the mixed solution is 98:1:0.5:0.5, and the mass ratio of LPSC, EC / LiFSI and polyvinyl carbonate / LiFSI in the obtained solid electrolyte membrane is 98:1:1.

[0104] Example 4

[0105] This embodiment provides a solid electrolyte membrane. The similarities with Example 1 are not repeated here. The difference from Example 1 is that the mass ratio of LPSC, EC / LiFSI, vinyl carbonate / LiFSI and diisopropyl peroxydicarbonate in the mixed solution is 90:9:0.5:0.5, and the mass ratio of LPSC, EC / LiFSI and polyvinyl carbonate / LiFSI in the obtained solid electrolyte membrane is 90:9:1.

[0106] Example 5

[0107] This embodiment provides a solid electrolyte membrane, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that the mass ratio of LPSC, EC / LiFSI, vinyl carbonate / LiFSI and diisopropyl peroxydicarbonate in the mixed solution is 90.4:9:0.1:0.5, and the mass ratio of LPSC, EC / LiFSI and polyvinyl carbonate / LiFSI in the obtained solid electrolyte membrane is 90.4:9:0.6.

[0108] Example 6

[0109] This embodiment provides a solid electrolyte membrane, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that the mass ratio of LPSC, EC / LiFSI, vinyl carbonate / LiFSI and diisopropyl peroxydicarbonate in the mixed solution is 90.4:9:0.5:0.1, and the mass ratio of LPSC, EC / LiFSI and polyvinyl carbonate / LiFSI in the obtained solid electrolyte membrane is 90.4:9:0.6.

[0110] Example 7

[0111] This embodiment provides a solid electrolyte membrane, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that the mass ratio of LPSC, EC / LiFSI, vinyl carbonate / LiFSI and diisopropyl peroxydicarbonate in the mixed solution is 94.5:4.9:0.1:0.5, and the mass ratio of LPSC, EC / LiFSI and polyvinyl carbonate / LiFSI in the obtained solid electrolyte membrane is 94.5:4.9:0.6.

[0112] Comparative Example 1

[0113] This comparative example provides a solid electrolyte membrane, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that during the coating process of the mixed solution, the scraper used has a specification of 300 μm, and after heating, a solid electrolyte membrane with a thickness of 112 μm is obtained.

[0114] Comparative Example 2

[0115] This comparative example provides a solid electrolyte membrane, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that the mass ratio of LPSC, EC / LiFSI, vinyl carbonate / LiFSI and diisopropyl peroxydicarbonate in the mixed solution is 94.5:4:1.3:0.2, and the mass ratio of LPSC, EC / LiFSI and polyvinyl carbonate / LiFSI in the obtained solid electrolyte membrane is 94.5:4:1.5.

[0116] Comparative Example 3

[0117] This comparative example provides a solid electrolyte membrane, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that the mass ratio of LPSC, EC / LiFSI, vinyl carbonate / LiFSI and diisopropyl peroxydicarbonate in the mixed solution is 94.5:4:0.3:1.2, and the mass ratio of LPSC, EC / LiFSI and polyvinyl carbonate / LiFSI in the obtained solid electrolyte membrane is 94.5:4:1.5.

[0118] Comparative Example 4

[0119] This comparative example provides a solid electrolyte membrane, and the similarities with Example 1 are not repeated here. The difference from Example 1 lies in that: hydrogenated styrene-butadiene block copolymer (SEBS) is dissolved in xylene solvent and heated at a temperature of 90-120°C for a heating time of 15-30 min to obtain a binder glue solution with a binder content of 5%; the electrolyte slurry and the above-mentioned binder glue solution are mixed, wherein the mass ratio of LPSC and SEBS is 94.5:5.5 and the solid content is 35% to obtain a mixed solution; the same coating film-forming method as in Example 1 is adopted to obtain a solid electrolyte membrane with a thickness of 15 um.

[0120] Comparative Example 5

[0121] This comparative example provides a solid electrolyte membrane, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that in the process of heating and film formation after the mixed solution is coated, the heating time is 6 hours to obtain a solid electrolyte membrane.

[0122] Comparative Example 6

[0123] This comparative example provides a solid electrolyte membrane, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that in the process of heating and film formation after the mixed solution is coated, the heating time is 24 hours to obtain a solid electrolyte membrane.

[0124] The solid electrolyte membrane obtained in the above embodiments and comparative examples was tested for ion conductivity. The testing equipment and method were as follows: the electrochemical workstation test frequency was set to 10 MHz-1000 Hz, the bias voltage was 0 V, the Z' value of the intersection of the straight line and the Z' axis was taken as the total impedance R of the solid electrolyte membrane, and the total ion conductivity was calculated according to the conductivity calculation formula σ = L / (R*S), L is the thickness of the sample, R is the total impedance, S is the effective area of ​​contact between the sample and the electrode. The test results are shown in Table 1:

[0125] Table 1

[0126]

[0127]

[0128] The solid electrolyte membrane obtained in the above embodiment and comparative example is applied to a solid-state battery, wherein the positive electrode active material is ternary nickel cobalt lithium manganese oxide, the negative electrode is metallic lithium, and the principle half-cell is assembled to test the first discharge specific capacity of the positive electrode at a rate of 0.1C. The test results are shown in Table 2:

[0129] Table 2

[0130]

[0131]

[0132] Referring to the test results in Table 1 and Table 2, combined with Examples 1, 2 and Comparative Example 1, it can be seen that as the thickness of the solid electrolyte membrane increases, the ionic conductivity and ionic conductivity retention rate of the solid electrolyte membrane decrease. Since the ionic conductivity of the ion conductive binder is relatively high, the lithium salt can increase the lithium ion concentration, which is beneficial to ion transport. Therefore, adjusting the thickness of the solid electrolyte membrane within the range of 5-100 μm has no significant effect on the ionic conductivity of the solid electrolyte membrane; when the thickness of the solid electrolyte membrane exceeds the set range, the ion migration path becomes longer, thereby reducing the ion migration efficiency of the ion conductive binder.

[0133] Combining Examples 1-7 with Comparative Examples 2 and 3, it can be seen that when there are too many polymer monomers or polymer initiators in the electrolyte, the conductivity of the solid electrolyte membrane is poor. In Comparative Examples 2 and 3, the mass proportion of the polymer in the solid electrolyte membrane increases, which affects the path of ion transmission, resulting in a decrease in the ionic conductivity of the solid electrolyte membrane, thereby affecting the coulombic efficiency of the solid-state battery having the solid electrolyte membrane.

[0134] Combining Example 1 with Comparative Example 4, it can be seen that the solid electrolyte membrane prepared in Comparative Example 4 does not include polymer and lithium salt, and the surface morphology of the solid electrolyte membrane prepared in Comparative Example 4 after isostatic pressing is as follows: Figure 2 As shown in FIG. 1 , the pore size of the solid electrolyte membrane surface is above 5 μm, that is, the gaps between the electrolyte particles are large, resulting in a loose structure and poor flexibility of the solid electrolyte membrane, and the binder filled between the electrolyte particles is not conductive, resulting in low ionic conductivity of the solid electrolyte membrane. The surface morphology of the solid electrolyte membrane prepared in Example 1 after isostatic pressing is shown in FIG. Figure 1 As shown, the pore size on the surface of the solid electrolyte membrane is below 1 μm. Under a pressure of 500 MPa, the structure of the solid electrolyte membrane is more compact after being subjected to mechanical stress, which further illustrates that the polymer can fill the gaps between the electrolyte particles, providing mechanical support for the solid electrolyte membrane, and is beneficial to increasing the compaction density of the solid electrolyte membrane, thereby further improving the application stability of the solid electrolyte membrane.

[0135] Combining Example 1 with Comparative Examples 5 and 6, it can be seen that when the heating time during the film formation process is insufficient, the polymerization reaction is insufficient, the polymer molecular chain is not fully formed or the molecular weight distribution is uneven, which in turn leads to a decrease in the performance of the polymer, affecting the mechanical strength and chemical stability of the solid electrolyte membrane; when the heating time during the film formation process is too long, excessive heating will destroy the structure of the electrolyte material and the binder, causing the binder to fail, and then causing the solid electrolyte membrane to dry and fall off, affecting the electrochemical properties and mechanical stability of the solid electrolyte membrane.

[0136] It should be noted that the various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0137] The above description has fully disclosed the specific implementation methods of the present application. It should be pointed out that any changes made by technicians familiar with the field to the specific implementation methods of the present application do not deviate from the scope of the claims of the present application. Accordingly, the scope of the claims of the present application is not limited to the above specific implementation methods.

Claims

1. A solid electrolyte membrane, characterized in that: The solid electrolyte membrane comprises an electrolyte material, an ion conductive binder and a polymer. The ion conductive binder comprises a binder and a lithium salt. The polymer is obtained by in-situ polymerization of polymer monomers during the membrane formation process.

2. The solid electrolyte membrane according to claim 1, characterized in that The solid electrolyte membrane satisfies at least one of the following characteristics: The mass ratio of the electrolyte material, the ion conductive binder and the polymer in the solid electrolyte membrane is 90-98:1-9:0.2-1; The mass ratio of the binder to the lithium salt in the ion conductive binder is 99-99.7:0.3-1.

3. The solid electrolyte membrane according to claim 1, characterized in that The thickness of the solid electrolyte membrane is 5-100 μm.

4. The solid electrolyte membrane according to any one of claims 1 to 3, characterized in that The solid electrolyte membrane satisfies at least one of the following characteristics: The polymer monomer includes at least one of vinyl carbonate, vinyl sulfite, vinylene trithiocarbonate, 1,3-propylene-sultone, propylene ethyl carbonate, diester of formate, allylphenyl carbonate, methyl methacrylate, and vinyl acetate; The electrolyte material includes at least one of an argyrodite-type sulfide solid electrolyte and a Thio-LIS ION-type sulfide solid electrolyte; The binder comprises at least one of ethyl cellulose, poly(1,4-butylene adipate), poly(ethylene butylene), polyacrylic acid and polyacrylonitrile; The lithium salt includes at least one of lithium hexafluorophosphate, bis(fluorosulfonyl)imide lithium salt, bis(trifluoromethanesulfonyl)imide lithium, and bis(pentafluoroethylsulfonyl)imide lithium.

5. The solid electrolyte membrane according to any one of claims 1 to 3, characterized in that: The electrolyte material satisfies at least one of the following characteristics: The argyrodite-type sulfide solid electrolyte includes Li6PS5X, wherein X includes at least one of Cl, Br, and I; The Thio-LISION type sulfide solid electrolyte includes (100-x)Li2S-xP2S5, Li4-yA-yB y S4, Li4SnS4 and X-doped Thio-LISION type sulfide solid electrolyte, wherein 0<X<100, A includes at least one of Ge and Si, B includes at least one of P, Al or Zn, 0<y<1, and x includes at least one of I and Br.

6. The method for preparing a solid electrolyte membrane according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Providing electrolyte slurry, ion conductive adhesive solution, polymer monomer solution and polymer initiator solution; The electrolyte slurry, the ion conductive binder, the polymer monomer solution and the polymer initiator solution are mixed according to a proportion, ground and dispersed to obtain a mixed solution; The mixed solution is coated on a bottom plate and heated to obtain a solid electrolyte membrane.

7. The preparation method according to claim 6, characterized in that: The electrolyte slurry comprises an electrolyte material and a solvent, and the electrolyte material accounts for 20% to 50% by weight of the electrolyte slurry.

8. The preparation method according to claim 6, characterized in that: The ion conductive adhesive glue comprises a binder, a lithium salt and a solvent, and the ion conductive adhesive satisfies at least one of the following characteristics: The binder and the lithium salt account for 5%-10% by mass in the ion conductive binder solution; The solvent includes at least one of xylene, trimethylbenzene, chlorobenzene, dichlorobenzene, trichlorobenzene, isobutyl isobutyrate, butyl acetate, anisole, and dibutyl ether.

9. The preparation method according to claim 6, characterized in that: The polymer monomer solution comprises a polymer monomer, a lithium salt and a solvent, and the polymer monomer solution satisfies at least one of the following characteristics: The mass ratio of the polymer monomer to the lithium salt is 99.5-99.7:0.3-0.5; The polymer monomer and the lithium salt account for 40%-60% by mass in the polymer monomer solution; The solvent includes at least one of xylene, trimethylbenzene, chlorobenzene, dichlorobenzene, trichlorobenzene, isobutyl isobutyrate, butyl acetate, anisole, and dibutyl ether.

10. The preparation method according to claim 6, characterized in that: The polymer initiator solution comprises a polymer initiator and a solvent, and the polymer initiator solution satisfies at least one of the following characteristics: The mass proportion of the polymer initiator in the polymer initiator solution is 10%-50%; The polymerization initiator includes at least one of benzoyl peroxide, diisopropyl peroxydicarbonate, azobisisobutyronitrile and tris(trifluoromethyl-sulfonate)aluminum.

11. The preparation method according to any one of claims 6 to 10, characterized in that: The preparation method meets at least one of the following characteristics: The mass ratio of the electrolyte material, the ion conductive binder, the polymer monomer and the polymer initiator is 90-98:1-9:0.1-0.5:0.1-0.5; The solid content of the mixed solution is 30%-50%; The mixing and grinding and dispersing processes are carried out at 10-20°C; The heating temperature is 90-120°C; The heating time is 10-16h.

Citation Information

Cited By

  • Polymer-based solid electrolyte and preparation method thereof

    CN120854668A

  • Sulfide composite solid electrolyte membrane and preparation method thereof

    CN121688074A